1989
DOI: 10.1192/s0007125000291514
|View full text |Cite
|
Sign up to set email alerts
|

The Positive and Negative Syndrome Scale (PANSS): Rationale and Standardisation

Abstract: Over 75 years ago, Bleuler (1911) confronted psychiatry with the question of ‘schizophrenia’ or ‘schizophrenias'. Today we recognise the heterogeneity of the condition, but we are still groping at efforts to clarify the different subtypes or subprocesses. Over the decades there have been various attempts to subclassify schizophrenia and tease apart the syndromes, none of which has been entirely successful. More recently, as a result of the work by Crow (1980) in England and Strausset al(1974) in the USA, it ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
518
0
13

Year Published

1991
1991
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 917 publications
(542 citation statements)
references
References 30 publications
1
518
0
13
Order By: Relevance
“…Since the peak intensity of D-9-THC effects were expected to occur between þ 10 and þ 80 timepoints and were expected to disrupt a subject's capacity to describe subjective effects, behavioral ratings were readministered 140 min after D-9-THC administration to capture D-9-THC effects retrospectively. Positive, negative, and general symptoms were assessed using the PANSS positive, negative, and general symptoms subscales of the Positive and Negative Symptom Scale (PANSS) (Kay et al, 1989). Perceptual alterations were measured using the Clinician Administered Dissociative Symptoms Scale (CADSS) (Bremner et al, 1998), a scale consisting of 19 self-report items and eight clinician-rated items (0 ¼ not at all, 4 ¼ extremely) that has been shown to be sensitive to the effects of other psychoactive drugs including ketamine (Krystal et al, 1994).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Since the peak intensity of D-9-THC effects were expected to occur between þ 10 and þ 80 timepoints and were expected to disrupt a subject's capacity to describe subjective effects, behavioral ratings were readministered 140 min after D-9-THC administration to capture D-9-THC effects retrospectively. Positive, negative, and general symptoms were assessed using the PANSS positive, negative, and general symptoms subscales of the Positive and Negative Symptom Scale (PANSS) (Kay et al, 1989). Perceptual alterations were measured using the Clinician Administered Dissociative Symptoms Scale (CADSS) (Bremner et al, 1998), a scale consisting of 19 self-report items and eight clinician-rated items (0 ¼ not at all, 4 ¼ extremely) that has been shown to be sensitive to the effects of other psychoactive drugs including ketamine (Krystal et al, 1994).…”
Section: Outcome Measuresmentioning
confidence: 99%
“…Symptomseverity was measured with the Positive and Negative Syndrome Scale (PANSS; Kay et al, 1989), which is considered the gold standard for the psychometric assessment of schizophrenia (Suzuki, 2011). The PANSS has good psychometric properties and is sensitive to change (Kay et al, 1989;Peralta and Cuesta, 1994;Santor et al, 2007). In order to avoid repetition of questions, both ratings were synthesized into one interview and not administered successively.…”
Section: Psychopathological Interviewmentioning
confidence: 99%
“…Psychometric studies have reported good inter-rater reliability and satisfactory internal consistency, construct validity and concurrent validity in relation to other measures of psychopathology (Kay et al, 1988;Kay et al, 1989). This measure was completed with participants at baseline and at 3 month post-baseline.…”
Section: Measures General Outcome Measuresmentioning
confidence: 99%